PENGARUH LIKUIDITAS, STRUKTUR MODAL, UKURAN PERUSAHAAN DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2015-2017) - Cicilia Amanda Tia Oktaviani, 17.05.72.0010; Srimindarti, Ceacilia (Students' Journal of Accounting and Banking, 2019)
The company’s main goal is maximize firm value. Firm value is good will be a positive signal for investors to invest their funds into the company. This study aims to examines the effect of liquidity, capital structure, firm size and dividend policy on firm value. This research was conducted at the Indonesia Stock Exchange by using a go public manufacturing company as the unit of analysis. The data analysis has been done by using multiple linear regression with the independent variables are liquidity, capital structure, firm size and dividend policy and the dependent variable is firm value. The sampling method uses purposive sampling with the observation period of 2015-2017 of 183 compnies. The analytical mehod used is multiple regression analysis, f test, t test and coefficient of determination analysis. The result of study indicate that simultaneously liquidity, capital structure, firm size and dividend policy has an influence on the firm value. The results of the study show that liquidity does not have a significant effect on firm value. Capital structure has a negative and significant effect on firm value. Firm size and dividend policy has a positive and significant effect on firm value.